Minimizing Open‐Circuit Voltage Loss in Perovskite/Si Tandem Solar Cells via Exploring the Synergic Effect of Cations and Anions. Issue 12 (7th December 2021) - He, Yongcai; Tang, Zeguo; Mao, Lin; Yang, Shaofei; Yang, Tian; Xie, Minghui; Chang, Qing; Ding, Lei; He, Bo; Peng, Chenwei; Yu, Cao; Hao, Xia; et al.
Abstract : In article number 2100119, Zeguo Tang, Yongzhe Zhang, and co‐workers discuss how adopting a perovskite/Si tandem solar cell structure is an effective approach to break the S–Q limit of single‐junction solar cells. Minimizing the open‐circuit voltage loss of the top perovskite solar cell is critical to achieving a high efficiency of the tandem cell because the open‐circuit voltage of the bottom Si cell is fixed, relatively, and the addition of MACl plays such a role.